A COMPREHENSIVE REVIEW ON EXPLORATION OF PHOTOVOLTAIC THERMAL TECHNOLOGY: PERFORMANCE ANALYSIS AND CONTEMPORARY ADVANCEMENTS (mLAC Journal for Arts, Commerce and Sciences (m-JACS) ISSN: 2584-1920, 2026)
With the accelerating biodiversity loss and escalating costs of traditional sources of energy, global attention is now focused on resilient and sustainable alternatives. Solar energy is the most affordable, clean, readily available, and ecologically friendly of the several renewable energy sources. Photovoltaic Thermal (PVT) technology is a major advancement in this field. It uses solar thermal collectors and photovoltaic (PV) cells in a synergistic way to generate electricity and collect useable heat energy simultaneously.Higher operating temperatures considerably diminish the electrical efficiency of conventional photovoltaic (PV) systems.By using a working fluid (such as water or air) to actively cool the PV cells, PVT systems solve this problem and increase electrical production while capturing waste heat. Researchers have created cutting-edge designs for heat collectors and novel PV materials to improve system performance overall.This paper presents a comprehensive review of PVT systems, highlighting their principle of operation, material advancements, categorization (air-based, water-based, nanofluid-based systems), and the range of analytical and experimental methods employed in their assessment. Additionally, the research highlights the technical and economic benefits of PVT systems and highlights their potential for large-scale, building-integrated use. The findings validate the contribution of PVT technology toward the development of the future of sustainable, high-efficiency solar energy solutions.
Keywords: PVT photovoltaic thermal cells, Solar energy, water and air